Stability result for fractional neutral stochastic differential system driven by mixed fractional Brownian motion. (15th December 2021) - Dhanalakshmi, K.; Balasubramaniam, P.
In this manuscript, stability result for fractional neutral stochastic differential system is established subject to mixed fractional Brownian motion (fBm). Sufficient condition for stability result is derived based on the pth mean square norm, fixed point theorem and help of new integral inequality. An example is also given to illustrate the effectiveness of the obtained theory.